GAMBARAN PENGGUNAAN KB IUD PADA IBU PASCA MELAHIRKAN DI RUANG BERSALIN BRSU WANGAYA - Noriani, Ni Ketut; Teja, Ayu Yulia Rewsati (Interdental: Jurnal Kedokteran Gigi, 2017)
Postpartum intrauterine device (IUD) is a contraceptive service provided directly to the patients after they give birth. Postpartum IUD is recommended because in this period the cervix remains open and soft, thus facilitate the IUD insertion. Women’s motivation is very important to bring success to the IUD postpartum program The aim of this study was to describe the motivation of postpartum mothers using IUD in the postpartum ward in Wangaya Hospital, 2016. This study was a descriptive, cross-sectional study. The sampling technique used non probability sampling (census), in which the total population was used as the sample. There were 30 respondents who have fulfilled the inclusion and exclusion criteria involved in this study. The result showed that the motivation of postpartum mothers using IUD in wangaya hospital in the postpartum ward was high (100%). All respondents in the postpartum ward, Wangaya Hospital Denpasar had a good understanding on the benefit of using the postpartum IUD, thus influence the high use of postpartum IUD.